2007
DOI: 10.1111/j.1365-2265.2007.02981.x
|View full text |Cite
|
Sign up to set email alerts
|

High molecular weight adiponectin dominates in cord blood of newborns but is unaffected by pre‐eclamptic pregnancies

Abstract: Adiponectin in cord blood from PE pregnancies may not be a tentative risk marker for Metabolic Syndrome-linked diseases. HMW adiponectin is the dominant form of adiponectin in cord blood. Its role during pregnancy and postnatal life should be further explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 32 publications
3
15
0
2
Order By: Relevance
“…28 Recently, adiponectin in cord blood has been described as predominantly in the HMW form. 29 Thus, the predominance of human milk adiponectin in the HMW form is consistent with both resistance to digestion and biological activity in the infant.…”
Section: Discussionmentioning
confidence: 83%
“…28 Recently, adiponectin in cord blood has been described as predominantly in the HMW form. 29 Thus, the predominance of human milk adiponectin in the HMW form is consistent with both resistance to digestion and biological activity in the infant.…”
Section: Discussionmentioning
confidence: 83%
“…That study included only 22 pregnancies with preeclampsia, and differences in adiponectin levels could not be reliably studied. In another Norwegian study, there was no difference in cord blood levels of adiponectin in the offspring of preeclamptic pregnancies and pregnancies without preeclampsia, after adjustment for length of gestation [26] . That study was hospital-based, and the comparison groups were rather small (30 preeclampsia and 62 control pregnancies).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study the most biological active isoform of adiponectin was found to represent the greatest part of total adiponectin in cord blood [26] . However, we do not know if this is the case in offspring of mothers with preeclampsia or in prematurely born offspring, and it would be of interest to study different isoforms of adiponectin in cord blood.…”
Section: Discussionmentioning
confidence: 99%
“…[47], показав, что у па-циенток с гестационной гипертензией и ПЭ, разви-вающейся в поздние сроки беременности, в первом триместре регистрируются значительно более низкие концентрации адипонектина по сравнению со здо-ровыми беременными из группы контроля. В дру-гих исследованиях не выявлено значимых различий в концентрациях адипонектина в ранние и поздние сроки гестации при развитии ПЭ и физиологической беременности [48]. Этиология таких противоречивых результатов остается до конца не выясненной.…”
Section: влияние адипонектина на инсулинорезистентность и развитие сиunclassified